2009
DOI: 10.1080/02652030802382253
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a new lateral flow immunochromatographic (LFIC) assay for the okadaic acid group of toxins using naturally contaminated bivalve shellfish from the Portuguese coast

Abstract: A new rapid assay for the okadaic acid group of toxins, based on lateral flow immunochromatographic (LFIC) test strips developed by Jellett Rapid Testing Ltd., was assessed on naturally contaminated bivalves from the Portuguese coast. One prototype was evaluated using samples harvested during 2005, extracted with 80% methanol, followed by dilution with the running buffer of a methanolic extract after alkaline hydrolysis for esters. The second prototype was assessed using samples harvested during 2006, extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In principle, this would enable shellfish industry to carry out these tests themselves. A recent study on these test trips showed that a relative high number of samples (45%) were misidentified as positive [ 126 ]. Further research is needed to make this LFI suitable for routine monitoring purposes.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…In principle, this would enable shellfish industry to carry out these tests themselves. A recent study on these test trips showed that a relative high number of samples (45%) were misidentified as positive [ 126 ]. Further research is needed to make this LFI suitable for routine monitoring purposes.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…The lateral flow immunoassay (LFIA) format has higher potential to meet the criteria for a rapid and simple test. However, previous attempts at developing a suitable LFIA have not possessed the desired speed, cross-reactivity, sensitivity, or accuracy in addition to notable matrix effects. ,, …”
Section: Introductionmentioning
confidence: 99%
“…However, previous attempts at developing a suitable LFIA have not possessed the desired speed, cross-reactivity, sensitivity, or accuracy in addition to notable matrix effects. 27,29,30 Furthermore, current extraction methods typically require relatively high solvent volumes, centrifugation, and in some cases expensive 0.2 or 0.45 μM membrane filtration, none of which were desired for a rapid and low-cost test.…”
Section: ■ Introductionmentioning
confidence: 99%